Quick guide to anime and manga - Henderson, Robert M. (ReferencePoint Press, 2022)
Describes the origins, development, and future of anime and manga. Highlights the appeal of the genre, and profiles popular shows and series. Includes color photographs, quotes, sidebars, and further resources.